Revitalizing the Pasai Sultanate Heritage: Negotiating Cultural and Religious Identity of Acehnese Society in the Modern Era - Aulia Rahman; Usman Usman; Mufti Riyani; Zulkifli Zulkifli; Okhaifi Prasetyo (IBDA` : Jurnal Kajian Islam dan Budaya, 2025)
As a foundational Islamic kingdom in the Indonesian archipelago, the Pasai Sultanate possesses a strategic heritage that remains underutilized in addressing contemporary challenges, such as the erosion of cultural identity, declining social tolerance, and low historical literacy. This study adopts a qualitative approach utilizing historical-interpretive analysis. Data were gathered through comprehensive documentary reviews of inscriptions and artifacts, field observations at heritage sites, and in-depth interviews with key stakeholders, including museum curators, educators, researchers, and the youth of North Aceh. The research offers three primary contributions: First, it identifies the strategic value of Pasai’s legacy as 'living heritage'—a dynamic symbol of a cosmopolitan civilization defined by tolerance and global integration. Second, it reveals a significant generational divide, wherein many young people perceive this legacy as static and disconnected from modern life. Finally, the study proposes an adaptive revitalization model built on three pillars: integrating the Pasai narrative into multicultural education, developing technology-driven heritage tourism, and leveraging digital media and creative industries to foster a sense of collective ownership.